2012
DOI: 10.1504/ijta.2012.046094
|View full text |Cite
|
Sign up to set email alerts
|

Social impacts of tourism as perceived by state-planned tourism destination residents: the case of Huatulco, Mexico

Abstract: Drawing from primarily quantitative data collected in 2010 among adult residents (n = 204) in the state-planned tourism destination of Huatulco, Oaxaca, Mexico, this paper examines the ways in which local residents perceive the social effects of regional tourism development. Currently, socio-demographic impacts of tourism are insufficiently addressed within developing economies and within tourism development initiatives crafted and implemented under state control. Field-tested questionnaire data and ethnograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
2
9
0
1
Order By: Relevance
“…This is due to the various laws among cities and municipalities that prohibits unwholesome activities. The findings mirrors the results of Monterrubio, Gullette, Ontiveros, Fernandez, & Luque's (2012) findings which stated that tourism does not contribute to crime, prostitution or drug. The findings in Table 16 shows that, despite the problems on solid waste disposal, the major attractions are kept clean and presentable.…”
Section: Impacts Of Tourism In the Province Of Cavitesupporting
confidence: 86%
“…This is due to the various laws among cities and municipalities that prohibits unwholesome activities. The findings mirrors the results of Monterrubio, Gullette, Ontiveros, Fernandez, & Luque's (2012) findings which stated that tourism does not contribute to crime, prostitution or drug. The findings in Table 16 shows that, despite the problems on solid waste disposal, the major attractions are kept clean and presentable.…”
Section: Impacts Of Tourism In the Province Of Cavitesupporting
confidence: 86%
“…At the same time, the development of tourism generates social harmony [30] and helps in the preservation of local cultures and the environment [31,32]. In-depth interviews conducted in Lombok, Indonesia also revealed that this sector produces many advantages, Sustainability 2019, 11,840 3 of 19 such as enriching residents' understanding of other cultures, strengthening their regional pride, and promoting local environmental protection [33]. That is, the development of tourism broadens residents' knowledge about transnational tourism, foreign countries, and people, thereby instilling a sense of pride in natives associated with their heritage and culture as well as contributing to the rehabilitation of existing buildings and historic sites and the transformation of old buildings to new uses [16,34].…”
Section: Tourism Development In the Developing Countriesmentioning
confidence: 99%
“…However, a booming tourism market also exerts negative influences on developing countries, and the negative sociocultural impacts on host communities have attracted increasing scholarly attention [9][10][11][12][13]. First, local culture and traditional values may be weakened by the acculturation and 2.…”
Section: Introductionmentioning
confidence: 99%
“…O 8 Estes dados respeitam o relatório de 2014 do WTTC disponível em http://www.wttc.org. 9 Ainda assim, uma situação próximo à recolhida por Monterrubio et al (2012) no México, onde também membros de grupos culturais diferentes representam 70% da força de trabalho da comunidade de Huatulco. ISSN 1984-4867 crescimento económico é uma realidade na ilha da Boa Vista, assim como se verificou nos trabalhos de Cooke (1982) O 'aumento dos níveis profissionais locais', prende-se com a capacitação profissional que a experiência e formação profissional no ramo da hotelaria e hospitalidade acarreta.…”
Section: Impactos Positivos Percecionados Pelos Residentesunclassified